2006
DOI: 10.1177/0032885505283876
|View full text |Cite
|
Sign up to set email alerts
|

Social Support, Gender, and Inmate Adjustment to Prison Life

Abstract: Although living in prison is difficult for all inmates, anecdotal evidence and a small number of qualitative studies on women's prisons suggest that females have greater social support needs while incarcerated. This claim is important for a more complete understanding of adjustment to prisons. In particular, extra and intrainstitutional social support mechanisms may reduce the inmate-perceived stresses associated with imprisonment and yield fewer official rule infractions. Using a multilevel analysis, the auth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
325
9
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(376 citation statements)
references
References 43 publications
34
325
9
8
Order By: Relevance
“…En lo que se refiere a la adaptación de los internos, se observa que el contexto carcelario conlleva más desajuste para los sujetos de mayor vulnerabilidad al ingreso en prisión, esto es, aquellos que presentan, por ejemplo, abuso de sustancias, problemas psicoemocionales en el contexto familiar o comportamentales precoces, mientras que el disponer de una relación marital facilita dicha adaptación (Jiang y Winfree, 2006). En este sentido, señalar que este resultado respalda el modelo de importación, el cual plantea que la cultura carcelaria importa há-bitos, valores y costumbres que la persona que entra en prisión ha adquirido previamente, y que influyen en los niveles de prisionización que presenta (Dhami, Ayton y Loewenstein, 2007;Paterline y Petersen, 1999).…”
Section: Discussionunclassified
“…En lo que se refiere a la adaptación de los internos, se observa que el contexto carcelario conlleva más desajuste para los sujetos de mayor vulnerabilidad al ingreso en prisión, esto es, aquellos que presentan, por ejemplo, abuso de sustancias, problemas psicoemocionales en el contexto familiar o comportamentales precoces, mientras que el disponer de una relación marital facilita dicha adaptación (Jiang y Winfree, 2006). En este sentido, señalar que este resultado respalda el modelo de importación, el cual plantea que la cultura carcelaria importa há-bitos, valores y costumbres que la persona que entra en prisión ha adquirido previamente, y que influyen en los niveles de prisionización que presenta (Dhami, Ayton y Loewenstein, 2007;Paterline y Petersen, 1999).…”
Section: Discussionunclassified
“…Six states of Australia and two territories implement their own governmental structures in association to the disciplinary facilities that they control (Jiang &Winfree, 2006). Provision of education facilities is made in the legislation and policies of all six states of Australia for the education accommodation of the children of imprisoned women.…”
Section: Availability Of Educational Facilities Provided To the Childmentioning
confidence: 99%
“…Previous studies on women's prison experiences [3][4][5][6]10] have demonstrated that control over privacy is a necessary condition for women to endure a prison sentence. When female detainees are unable to establish a sufficient level of privacy within their immediate environment, such as their own cell, this may lead to self-destructive behaviour [10], although there is also some evidence that too much privacy leads to self-harm and suicide ideation (see [5,27]).…”
Section: Survival In Theorymentioning
confidence: 99%
“…A relatively large amount of research has been conducted on the prison experiences of women [1][2][3][4][5][6][7][8][9][10], but as far as we know, very little field research has been done by researchers on the experiences of women incarcerated in a foreign country. The research on which this article is based deals with Dutch women detained in prisons in Peru.…”
Section: Introductionmentioning
confidence: 99%